Kobieta jako desygnat przedmiotu czynności wykonawczej przestępstw przeciwko rodzinie i opiece - Jurewicz, Justyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The text shows the problem of a woman as an object of the chosen offences against family an guardianship in Polish Penal Code. The author claims that in spite of the fact of wider circle of victims of described offences, mainly the woman is the one who suffers very often, more often than other cathegories of objects of these offences. The author gives some proposals of changing the point of view onto the women as the weak human beings. The text also offers the practical cases
Keywords: woman; object of the offence; avoiding financial support; abuse